ANALYSIS OF NPL OF CONVENTIONAL COMMERCIAL BANKS SEEN FROM CAR, LDR, ROA, AND BOPO LISTED ON IDX - Lisra; Yahya; Salida, Amrizal (Paser Institute Of Accounting and Finance, 2023)
Credit analysis was carried out to uncover problems that might occur in conventional banks listed on the Indonesia Stock Exchange (BEI) in the period 2019 to 2021. This research considers several indicators, namely CAR (Capital Adequacy Ratio), LDR (Loan to Deposit Ratio ) ), ROA (Return on Assets), and BOPO (Operating Costs to Operating Income). The method used in this research is the saturated sampling method, where the entire research population consisting of 43 companies was taken as a sample. The data used as the basis for research comes from financial reports and annual reports of these companies. Analysis was carried out using descriptive techniques, classical hypothesis testing, and multiple linear regression testing. The research results show that non-performing loans (NPL) are influenced by the return on assets (ROA) of Indonesian conventional banks but are not influenced by the capital adequacy ratio (CAR), loan-to-deposit ratio (LDR), operational costs (BOPO), and income. Conventional bank operations registered on the IDX. This provides important insight into the factors that influence the credit performance and financial stability of conventional banks in Indonesia and can be a basis for making decisions in credit risk management in the future.